HIV Status and Risk Factors for Hypertension in South African Adults - Hubber, Jennifer Marie (My University, 2016)
Background: As treatment innovations increase the life expectancy of those with HIV, the relationship between HIV infection, hypertension risk and subsequent CVD is increasingly important to understand. We investigated the relationship between HIV infection and hypertension among a cohort of ART-naïve South African adults presenting for voluntary HIV screening. Methods: We conducted a cross-sectional, observational study among adults (≥18 years) presenting for voluntary HIV testing in an urban township of KwaZulu-Natal, South Africa. We measured resting blood pressure prior to HIV testing among the entire cohort. We then measured another resting blood pressure among HIV-infected adults after they received their HIV test result and a clinical examination. We defined hypertension as having a resting systolic blood pressure ≥ 140 mmHg or a diastolic blood pressure ≥ 90 mmHg. We used logistic regression to analyze the risk factors for hypertension among both the entire cohort and among HIV-infected adults, to describe the association between HIV infection, CD4 count, and hypertension. Results: Among 2,904 adults screened for hypertension, mean age was 31.0 years (SD=9.66), 51.0% were female, and 37.9% screened positive for HIV. Diastolic blood pressure was significantly higher after HIV testing, among those testing HIV-positive. In univariate analyses among the entire cohort, older age, male sex, current marriage, having >1 child, higher income, and alcohol use were all significantly associated with hypertension. In a multivariate model, older age, male sex, alcohol use and HIV infection were independently associated with a higher odds of hypertension. In this model, being HIV-positive was associated with a 30% lower odds of having hypertension, compared to those testing HIV-negative (aOR=0.70, 95% CI: 0.54, 0.90, p=0.006). In a separate univariate model restricted to the HIV-positive adults, older age, current marriage, having >1 child, glucose level ≥120 mg/dl, obesity (body mass index >=30 kg/m2), and CD4 count above the median 300 cells/mm3 were all significantly associated with hypertension. In a multivariate model for this subgroup, older age, obesity (body mass index >=30 kg/m2), and CD4 count above 300 cells/mm3 were independently associated with a higher odds of having hypertension. In this model, CD4 count above 300 cells/mm3 was found to be associated with 78% higher odds of having hypertension, compared to those with a CD4 <300 (aOR=1.78, 95% CI: 1.13, 2.80, p=0.013). Conclusions: At HIV screening, HIV-infected adults had lower odds of hypertension, compared to those testing HIV-negative, after adjustment for other risk factors; among HIV-positive participants, those with lower CD4 counts had lower odds of hypertension. Screening for chronic hypertension at HIV diagnosis may be masked by HIV-status and severe immunosuppression, so a general approach to CVD screening for hypertension at HIV diagnosis may not reflect the true population risk.
Thesis (Master's)--University of Washington, 2016-06
Keywords: HIV; hypertension; South Africa; Epidemiology; epidemiology